2007
DOI: 10.1016/j.foodcont.2005.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance profile of Staphylococcus aureus isolated from raw meat: A research for methicillin resistant Staphylococcus aureus (MRSA)

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) has emerged as a risk factor for patients in general population and particularly in immunocompromised patients. As a matter of fact, it can produce serious infections that may then evolve in septicaemia. However, transmission of MRSA from food to people can represent a serious problem only for immunocompromised people. Vancomycin is the elective antimicrobial commonly used in case of MRSA infection, but S. aureus strains with reduced sensibility to vancomycin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
114
2
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(149 citation statements)
references
References 27 publications
(26 reference statements)
29
114
2
4
Order By: Relevance
“…Erythromycin resistance found in our study was higher than that observed by Bertollatti et al (2003). Vancomycin resistance determined in the study by Pesavento et al (2007) was similar to that found in our study whereas important differences occurred in tetracycline resistance. Duman (2007) found that erythromycin, tetracycline, and chloramphenicol resistances were different from ours while vancomycin and ciprofloxacin resistances of S. aureus were similar to ours.…”
Section: Antibiotic Resistance Of Staphylococcus Aureus Strainssupporting
confidence: 87%
See 1 more Smart Citation
“…Erythromycin resistance found in our study was higher than that observed by Bertollatti et al (2003). Vancomycin resistance determined in the study by Pesavento et al (2007) was similar to that found in our study whereas important differences occurred in tetracycline resistance. Duman (2007) found that erythromycin, tetracycline, and chloramphenicol resistances were different from ours while vancomycin and ciprofloxacin resistances of S. aureus were similar to ours.…”
Section: Antibiotic Resistance Of Staphylococcus Aureus Strainssupporting
confidence: 87%
“…The development of resistance both in human and animal bacterial pathogens has been associated with the extensive therapeutic use of antimicrobials or with their administration as growth promoters in food animal production (Normanno et al 2007). Antibiotics have been extremely useful for the treatment of infectious diseases in the last 50 years and have become indispensable for the treatment of many diseases formerly known as lethal (Pesavento et al 2007). The use of antibiotics and other antimicrobial agents throughout the food chain contributes to the emergence of resistant bacteria that can be passed directly to humans after ingestion (Demirtürk & Demirdal 2004;Ruzauskas et al 2010).…”
mentioning
confidence: 99%
“…Transfer of antibiotic resistance from human to animal isolates or the other way around has been a major concern (Pesavento et al, 2007;Zadoks et al, 2002). Host specificity of clones may reduce the chance that human-derived antibiotic-resistant S. aureus isolates are transmitted to cattle, although bovine mastitis may occasionally be caused by human-derived isolates.…”
Section: Discussionmentioning
confidence: 99%
“…The usage of antibiotics correlates with the emergence and maintenance of antibiotic resistant traits within pathogenic strains [9].…”
Section: Introductionmentioning
confidence: 99%